The French revolution and the transfer of the open access order to the South-Western German states and Prussia - Joachim Zweynert (Hamburgisches WeltWirtschaftsInstitut (HWWI), 2010)
Twenty years after the fall of the Iron Curtain, there is again a debate on shock therapy versus gradualism, this time with regard to developing and emerging societies. This debate was mainly triggered by Dani Rodrik (2007), who argues that reform programmes in poor countries should not be implemented according to a one fits all development blueprint (such as the Washington Consensus) but should try to relate to the specific conditions of time and space - a strategy calling for gradualism and the participation of local actors. Daron Acemoglu et al. (2009) have recently undertaken a forceful attempt to refute this view. In their paper The Consequences of Radical Reform: The French Revolution the authors provide empirical evidence of the lasting growth-stimulating impact of the implementation of the Napoleonic Code and other post-revolutionary institutional innovations in other European countries and in particular in those parts of Germany that were occupied by France. As these changes were introduced at high speed and followed a radical top-down approach, the authors regard them as proof that it is certainly not always necessary to adapt reforms to local circumstances and that shock therapy in certain institutional contexts is often the only means to break the hold on land and people exercised by the ancient regime (Acemoglu et al. 2009, p. 6). The present paper was originally intended as an extended comment on Acemoglu et al. Its aim, however, was never to refute their thesis but, rather, to complement their analysis.
Keywords: 330